How Teacher Creativity Brings to Indonesian Language Teaching Innovations in The Multimedia Era - Mas'ud Muhammadiah; Stephanus Turibius Rahmat; Endang Fatmawati; Arif Bintoro Johan; Petrus Jacob Pattiasina (Nazhruna: Jurnal Pendidikan Islam, 2022)
Teacher creativity determines the success of teaching Indonesian through innovative activities, especially in the multi-media era, which has become part of teaching for all subject areas. For this reason, we have conducted a literature search on several data found by experts in teaching Indonesian language education, both sourced from national and international journal publications and other sources that support Indonesian language teaching programs through creativity and innovation by involving multi-media. So that we can use the data in answering the questions and objectives of this study, we first examined the data by involving a phenomenology-based approach, an approach that seeks to explore as much data as possible to obtain comprehensive, high-quality answers to the study problem. Based on the exposure and discussion of our findings after understanding that teachers' creativity in teaching Indonesian will determine learning outcomes combined with innovative learning methods and strategies in line with the demands of the current multi-media era. Thus, the results of this study will become an essential input in supporting the study and development of teaching Indonesian as the national language in Indonesia in the technological era.